Construction of some new families of nested orthogonal arrays. Issue 3 (1st February 2019) - Zhang, Tian-fang; Wu, Guobin; Dey, Aloke
ABSTRACT: Nested orthogonal arrays have been used in the design of an experimental setup consisting of two experiments, the expensive one of higher accuracy being nested in a larger and relatively less expensive one of lower accuracy. In this paper, we provide new methods for constructing two types of nested orthogonal arrays.